Numerical study on the influence of salt marsh plants on coastal wetland hydrodynamics and suspended sediment transport - Jiang, Hengzhi; Chai, Chongxu; Zhang, Mingliang (Frontiers in Environmental Science, 2023)
Salt-marsh plants play important roles in the hydrodynamics and sediment transport and deposition processes in coastal regions. The Delft3D model was applied to quantify the influence of salt-marsh plants on the hydrodynamic characteristics and suspended sediment transport of a coastal wetland, and to reveal the contribution of plants in trapping sediment in the local area. Specifically, the spatial distributions of salt-marsh plants were acquired from remote sensing images and coupled with the Delft3D model. A comparison showed that the modeled results and observed data fit very well. The model results indicated that salt marsh plants had a negligible effect on tidal level, but they did significantly affect flow velocity and tidal flux, as indicated by the obvious slow-flow zones in vegetated belts. Phragmites australis attenuated the flow velocity more than Suaeda heteroptera. We also found that the suspended sediment concentration was lower in Phragmites australis and Suaeda heteroptera areas because the resistance created by vegetation prevented sediment from being resuspended and helped trap suspended sediment. Numerical experiments further confirmed that the suspended sediment flux was obviously different with and without vegetation. The interception of suspended sediment by salt marsh plants could reduce the suspended sediment by more than 60%.